(3QSGdI aj YOO Bi GdbQBf hcdeGJg hMQha LedIs ((3CMeO QaYJ s)
(3ChdgG (B:s
(3YO Bi GdbQBf Ydi eGbGdg Ydi QVi Gddg Yfg hGdchajhf hgh GdeNJGQ SJI BdGa heGFJGf hSJI hKdGKhf BjI s
(3BNQgG (B:s
(3hYf YHO GdYRjR Hf YHO Gddg MQha GdbQBf KdKeGFI Cda hEMOi YTQ Cda heGFJGf MQakG hHGddg GdJhajb JeJ s
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs